Role of the village head in handling inheritance disputes outside the court in the customary inheritance law of the Osing Tribe (Blambangan) (Study in Kemiren Village, Glagah District, Banyuwangi Regency) - Arief Yudistira (Central Research Institute for Agriculture (CeRIA), 2022)
The approach method used is sociological juridical, namely research that analyzes the role of the village head in society in relation to the applicable customary inheritance law. Research specifications using descriptive qualitative data analysis method, namely analytical methods based on field data and studies of problems in the literature. Based on the results of the research, the answers to the existing problems were obtained: (1) Efforts made by the Village Head were to find family trees from the parties, collect information regarding the origins of disputed assets, initiate deliberation meetings, propose alternative solutions to problems, provide necessary suggestions. (2) Inhibiting factors in dispute resolution, namely: it is difficult to know the status of the inheritance, constraints regarding limited witnesses, the human factor, the transfer of ownership rights to land without being recorded. Supporting factors in dispute resolution are: the Village Head has very strong influence, the attitude of the village community that views inheritance disputes as a disgrace, deliberations are conducted in a spirit of kinship, disputes in the District Court are considered more complicated, cost a lot and take a long time. In response to this, if in the distribution of inheritance there is a dispute, deliberations should always be held in the spirit of kinship and harmony to find the best solution that can be accepted by all parties. Counseling and cooperation with NGOs or with official institutions related to land disputes should continue to be pursued, so that people's knowledge will increase and therefore it is hoped that it can minimize inheritance disputes.